Diversity in Systems Engineering Special Feature Introduction. Issue 3 (12th November 2019) - Hoverman, Lisa; Long, David; Squires, Alice F.
ABSTRACT: This inaugural special edition on 'Diversity in Systems Engineering' explores the role of the systems engineering community in embracing diversity, equity, and inclusion as key enablers in the systems approach. As master integrators, systems engineers are accountable for delivering optimal affordable system solutions to complex problems. To do so requires more than an understanding of technology. It requires an understanding of people and social systems ‐ culture and the impact of cultural barriers, the cost of gender inequity, the need for cognitive and idea diversity, and a path to achieve inclusivity by design to name just a few areas. These represent a sample of the topics addressed in this special edition, where authors share their past experiences and forward thinking on the role of diversity, equity, and inclusion in developing systems and global systems engineering leadership.